Comparison Of Intrathecal Bupivacaine With Nalbuphine And Bupivacaine With Fentanyl In Inguinal Hernia Surgery (Indian Journal of Applied-Basic Medical Sciences, 2020)
CONTEXT Opioids as an adjuvant to hyperbaric Bupivacaine improves perioperative analgesia with  minimal side effects. AIM-The aim of the study is to compare the effect of intrathecal Nalbuphine and Fentanyl as  adjuvants to hyperbaric Bupivacaine on onset and duration of sensory blockade, onset and  duration of motor blockade, two segment sensory regression time, duration of effective  postoperative analgesia and incidence of side effects. STUDY DESIGN Prospective observational study ETHICAL ASPECT AND METHODS After all ethical committee clearance and written informed consent, 60 patients of ASA  grade I and II undergoing inguinal hernia surgery will be randomly divided into two groups: Group I – 0.5 % Bupivacaine(heavy) 3 ml + Nalbuphine 0.1 ml (1 mg) and Group II – 0.5%  Bupivacaine(heavy) 3 ml + Fentanyl 0.5 ml (25 µg). RESULT There was no significant difference in onset ofsensory and motor blockade.Duration of sensory blockade was significantly prolonged (111.42 ± 9.21 min) in Group I than in Group II  (102.32 ± 6.45 min) and duration of motor block was significantly extended in patients of  Group I(144.65± 15.12 min) than Group II (130.42 ±11.12 min). The duration of effective  analgesia was significantly more in group I than group II, with no significant side effects. CONCLUSION-1 mg Nalbuphine in 3 ml 0.5% hyperbaric Bupivacaine in patients increases the duration of sensory and motor block as compared to Fentanyl as well as provides effective  analgesia time more than Fentanyl in patients scheduled for inguinal hernia surgery under  subarachnoid block.
Keywords: Bupivacaine; Fentanyl; Nalbuphine; Spinal Anaesthesia; Inguinal Hernia Surgery